2020
DOI: 10.3390/nano10091692
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Biocompatible Polycaprolactone and Copper Oxide Nanoparticle Wound Dressings against Methicillin-Resistant Staphylococcus aureus

Abstract: One of the major health problems linked to methicillin-resistant Staphylococcus aureus (MRSA) is severe diabetic foot ulcers (DFU), which are associated with hospital-acquired infections, lower limb amputations and emerging resistance to the current antibiotics. As an alternative, this work aims to develop a biodegradable and biocompatible material with antimicrobial capacity to prevent DFU. This was achieved by producing active polymeric films with metallic nanoparticles dispersed through a polycaprolactone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 66 publications
2
31
0
1
Order By: Relevance
“…Figure 4(a) depicts E. faecalis , S. aureus , and P. aeruginosa bacterial survivability on PCL/Gel and PCL/Gel/Chrysin, with green representing living bacteria and red indicating dead bacteria. According to Figure 4(b) , the bacteria on the PCL were nearly entirely alive, showing that the PCL and gelatin in the scaffold lacked antibacterial characteristics consistent with prior studies [ 46 49 ]. In comparison, bacteria on PCL/Gel/Chrysin had a very poor bacterial population survival rate of less than 16% in all categories.…”
Section: Resultssupporting
confidence: 83%
“…Figure 4(a) depicts E. faecalis , S. aureus , and P. aeruginosa bacterial survivability on PCL/Gel and PCL/Gel/Chrysin, with green representing living bacteria and red indicating dead bacteria. According to Figure 4(b) , the bacteria on the PCL were nearly entirely alive, showing that the PCL and gelatin in the scaffold lacked antibacterial characteristics consistent with prior studies [ 46 49 ]. In comparison, bacteria on PCL/Gel/Chrysin had a very poor bacterial population survival rate of less than 16% in all categories.…”
Section: Resultssupporting
confidence: 83%
“…The analysis of the previous reports shows the growing interest in modifying PCL films/coatings to obtain biodegradable materials, which can be antimicrobial agent release carriers, e.g., antimicrobial peptides [39] or antibiotics [37]. Moreover, work is underway on composite materials with appropriate antimicrobial activity, which are obtained by introducing an inorganic agent, such as ZnO and CuO, into the PCL matrix [40]. The use of the PCL/TiO 2 system is especially interesting in the production of composite fibers using the electrospinning method [41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Further, they also observed that the cell morphology of candida was disrupted in a dosedependent manner on the infused mat 98 . The toxicity of copper ions released from nanoparticles on mammalian cells along with bacterial cells was first reported by Balcucho et al 99 . They They observed that coating remarkably improved the antibacterial potential of the scaffold 100 .…”
Section: Copper Oxidementioning
confidence: 94%